EFFECT OF ASSOCIATION OF DOUGH CHARACTERISTICS WITH STORAGE PROTEINS OF WHEAT AND GRAM FLOURS ON TEXTURE OF THE LEAVENED FLAT BREAD (NAAN) - Z. Farooq; S. U. Rehman; M. U. I. Khan (Journal of Animal and Plant Sciences, 2014)
The flours of Pakistani wheat varieties/lines were evaluated for their dough characteristics (farinographic) and protein subunits (PAGE) associated with the texture of the end-product (naan). Based on these studies varieties LU-26 and LU-31 were selected for supplementation with 5, 10, 15, 20 and 25% gram (chickpea) flour to improve protein. The composite flours were further evaluated for protein subunits and associated with the texture of the composite flour naans. The storage protein subunits ω-gliadin, and Low Molecular Weight (LMW) albumins and globulins showed a positive correlation with the water absorption and softening of the dough. The texture of the product also showed a strong relationship with the glutenin, gliadin and albumin subunits of simple wheat flours. The addition of the gram flour into wheat flour caused proportionate increase in intensity of all protein subunits which exhibited a negative correlation with the texture of the composite flour naans for both varieties.
Keywords: Flour; Chickpea; Farinograph; Proteins; Bread; Texture